Relationship between the vertical countermovement jump and the simulated performance of the initial 15 meters of crawl swimming performed by adolescent athletes - Fernanda Cristina Silva de Oliveira; Guilherme Pereira de Oliveira; Mateus Freitas de Medeiros; Pablo Henrique Moura de Paiva; Alexandre Bulhões-Correia; Paulo Francisco de Almeida Neto; Breno Guilherme de Araújo Tinôco Cabral (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2023)
Background: The start in swimming occurs via a jump that propels the swimmer into the pool. The relationship of the power generated by the start jump to first 15-m performance in swimming events is not yet known. Objective: Verify the correlation of the countermovement vertical jump (CMJ) with the simulated start performance of the crawl swimming. Materials and Methods: The present research was observational pilot study. The sample consisted of 12 Brazilian swimmers aged between 12 and 16 years (male). The CMJ was analyzed by a specific Platform for Jump Testing. Afterward, the athletes were directed to an Olympic swimming pool and positioned themselves in the starting block. Then, at the sound signal (whistle), they swam the first 15 meters of the pool in crawl style at the highest possible speed to simulate the start of the competition of swimming. Results: Thus, the study showed a negative correlation of the CMJ with the simulated start of 15 meters in the crawl style (r =-0.816; p=0.001). The analyses indicated that the CMJ contributes 66% (F (1.10) = 19.92; p=0.001) for the performance of 15 meters during the simulated start of the crawl stroke. It was shown that for every 1 cm increase in CMJ height, there was an improvement of 0.0885 milliseconds in swimming performance. Conclusion: CMJ is associated with the variation of the sprint time during the simulated start of a swimming test in the crawl swimming style.